The Readibility of Articles in Electronic Book for Schools Indonesian Language Textbook - Imam Safi'i; Wini Tarmini; Sobri Sobri (IKIP PGRI Bojonegoro, 2021)
The purpose of this study is to describe the readability rate of articles contained in Electronic Book for Schools (EBS), Indonesian Language textbook for High School students, The author is using Flesch Formula technique in measuring the readability of the articles, which is “RE = 206,835 – (1,015 ASL) – (84,6 ASW)”, In The said analysis, we take two paragraphs from each article as a sample for the measurement of the readability, Based on our study, we know that the average readability of an article in Electronic Book for Schools (EBS), Indonesian Language textbook is very low, which is -15,79, The result of this research can be utilized as the basis in choosing articles or texts for reference materials in teaching Indonesian language for high school students,Abstrak Tujuan penelitian ini adalah untuk menggambarkan tingkat keterbacaan artikel yang terkandung dalam Buku Sekolah Elektronik (BSE), buku teks Bahasa Indonesia untuk siswa SMA, Metode yang digunakan untuk mengukur tingkat keterbacaan adalah dengan menggunakan Formula Flesch, yaitu